Axitinib plus pembrolizumab in patients with advanced sarcomas including alveolar soft-part sarcoma: a single-centre, single-arm, phase 2 trial. Issue 6 (June 2019) - Wilky, Breelyn A; Trucco, Matteo M; Subhawong, Ty K; Florou, Vaia; Park, Wungki; Kwon, Deukwoo; Wieder, Eric D; Kolonias, Despina; Rosenberg, Andrew E; Kerr, Darcy A; Sfakianaki, Efrosyni; Foley, Mark; et al.
Summary: Background: VEGF promotes an immunosuppressive microenvironment and contributes to immune checkpoint inhibitor resistance in cancer. We aimed to assess the activity of the VEGF receptor tyrosine-kinase inhibitor axitinib plus the anti-PD-1 immune checkpoint inhibitor pembrolizumab in patients with sarcoma. Methods: This single-centre, single-arm, phase 2 trial was undertaken at a tertiary care academic medical centre in Miami, FL, USA, and participants were recruited from all over the USA and internationally. Patients were eligible if they were aged 16 years or older, and had histologically confirmed advanced or metastatic sarcomas, including alveolar soft-part sarcoma (ASPS); measurable disease with one site amenable to repeated biopsies; an ECOG performance status of 0–1; and progressive disease after previous treatment with at least one line of systemic therapy (unless no standard treatment existed or the patient declined therapy). The first five patients were enrolled in a lead-in cohort and were given axitinib 5 mg orally twice daily and pembrolizumab 200 mg intravenously for 30 min on day 8 and every 3 weeks for cycles of 6 weeks for up to 2 years. Thereafter, patients received escalating doses of axitinib (2–10 mg) plus flat dose pembrolizumab according to the schedule above. The primary endpoint was 3-month progression-free survival. All patients were evaluable for survival and safety analyses. This study is registered withClinicalTrials.gov, numberNCT02636725, and is closed to accrual. Findings: Between April 19, 2016, and Feb 7, 2018, of 36 patients assessed for eligibility, 33 (92%) were enrolled and given study treatment (intention-to-treat population and safety population), 12 (36%) of whom had ASPS. With a median follow-up of 14·7 months (IQR 10·1–19·1), 3-month progression-free survival for all evaluable patients was 65·6% (95% CI 46·6–79·3). For patients with ASPS, 3-month progression-free survival was 72·7% (95% CI 37·1–90·3). The most common grade 3 or 4 treatment-related adverse events included hypertension (five [15%] of 33 patients), autoimmune toxicities (five [15%]), nausea or vomiting (two [6%]), and seizures (two [6%]). Serious treatment-related adverse events occurred in seven (21%) patients, including autoimmune colitis, transaminitis, pneumothorax, haemoptysis, seizures, and hypertriglyceridemia. There were no treatment-related deaths. Interpretation: Axitinib plus pembrolizumab has manageable toxicity and preliminary activity in patients with advanced sarcomas, particularly patients with ASPS, warranting further investigation in randomised controlled trials. Funding: Merck, Pfizer, American Cancer Society, and Sylvester Comprehensive Cancer Center.